Rap1 maintains adhesion between cells to affect Egfr signaling and planar cell polarity in Drosophila. - O'Keefe, D.D.; Gonzalez-Niño, E.; Burnett, M.; Dylla, L.; Lambeth, S.M.; Licon, E.; Amesoli, C.; Edgar, B.A.; Curtiss, J. (Developmental Biology, 2009)
The small GTPase Rap1 affects cell adhesion and cell motility in numerous developmental contexts. Loss of Rap1 in the Drosophila wing epithelium disrupts adherens junction localization, causing mutant cells to disperse, and dramatically alters epithelial cell shape. While the adhesive consequences of Rap1 inactivation have been well described in this system, the effects on cell signaling, cell fate specification, and tissue differentiation are not known. Here we demonstrate that Egfr-dependent cell types are lost from Rap1 mutant tissue as an indirect consequence of DE-cadherin mislocalization. Cells lacking Rap1 in the developing wing and eye are capable of responding to an Egfr signal, indicating that Rap1 is not required for Egfr/Ras/MAPK signal transduction. Instead, Rap1 regulates adhesive contacts necessary for maintenance of Egfr signaling between cells, and differentiation of wing veins and photoreceptors. Rap1 is also necessary for planar cell polarity in these tissues. Wing hair alignment and ommatidial rotation, functional readouts of planar cell polarity in the wing and eye respectively, are both affected in Rap1 mutant tissue. Finally, we show that Rap1 acts through the effector Canoe to regulate these developmental processes.